(untitled) (LACCEI, 2024)
The objective of this research was to currently propose the application of a transport optimization and control model in the port of Callao, thereby evaluating the port management systems and the specific objectives were to answer the research question by evaluating possible solutions to be able to improve the productivity of the port of Callao and of the main transport companies that frequent the port terminal. This analysis is performed using academic information sources, under the systematic review methodology considering databases and search equations and inclusion and exclusion criteria as a strategy. The results show that the implementation of the project is currently reliable, thus constant monitoring is very important since it helps to maintain the pace of work and find possible solutions to sudden situations that may arise over time. Research in management systems in port and transport terminals worldwide is related to: Logistics, Environmental Management, Risk Management, Inventory Management and Occupational Health and Safety.